Comparison of preoperative and postoperative frailty in elderly following gastrointestinal cancer surgery - Ozdemir, Gorkem; Sözütek, Alper (The European Research Journal, 2025)
Objectives: This study aimed to compare preoperative and postoperative frailty status in patients undergoing elective gastrointestinal cancer surgery using the FRAIL (Fatigue, Resistance, Ambulation, Illness, and Loss of weigh) and Clinical Frailty Scale (CFS) indices and to determine the relationship between frailty and early postoperative complications as well as surgical outcomes. Methods: This prospective study included patients aged 65 years and older who underwent elective gastrointestinal cancer surgery. Preoperative and early postoperative frailty assessments were conducted using the FRAIL and CFS scores. Statistical analyses were conducted to investigate the association between frailty scores and surgical/clinical outcomes. Results: Of the 91 patients included in the studythe mean age was 70.9±6.1 years (range: 65-75). The mean FRAIL score increased postoperatively (1.9±1.2 preoperatively to 2.3±1.5 postoperatively, Δpost-pre: 0.4±0.9, P